Dostosowanie wzorców działania inwestora zagranicznego do warunków rynków wyłaniających się w świetle teorii gier - Dziubińska, Agnieszka; Borczuch, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Market entry of foreign investor is connected with problem of perceived familiarity with local business environment. Game theory offers useful instruments and tools in decision making process as emerging markets force foreign corporations to reinvent patters of activities. In this paper, the authors present a process of adjustment as a decision making factor in uncertainty circumstances. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 253-259